2004
DOI: 10.1136/jcp.2004.018713
|View full text |Cite
|
Sign up to set email alerts
|

Plasma nitrotyrosine in reversible myocardial ischaemia: Table 1

Abstract: Background: Nitric oxide (NO) plays a vital role in vascular homeostasis and in the pathophysiology of coronary heart disease. Its metabolites, nitrite and nitrate, have vasculoprotective properties, whereas peroxynitrite, an oxidant metabolite of NO, is cytotoxic and can aggravate myocardial damage during ischaemic reperfusion injury. Peroxynitrite nitrates free and protein bound tyrosine residues to produce nitrotyrosine. The measurement of nitrotyrosine provides an indirect estimation of plasma peroxynitrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…As few biomarkers can detect transient myocardial ischemia, serum NT could be a biomarker for detecting this condition in patients with VSAP. One study has found that plasma NT does not increase at 30 min after a positive exercise tolerance test [34]. The decreased duration and extent of ischemia after exercise might have been insufficient to elevate NT levels in that study.…”
Section: Discussionmentioning
confidence: 57%
“…As few biomarkers can detect transient myocardial ischemia, serum NT could be a biomarker for detecting this condition in patients with VSAP. One study has found that plasma NT does not increase at 30 min after a positive exercise tolerance test [34]. The decreased duration and extent of ischemia after exercise might have been insufficient to elevate NT levels in that study.…”
Section: Discussionmentioning
confidence: 57%
“…[90] 0.6 LC-MS/MS N.R./N.R. [91] <0.4 LC-MS/MS 22 fmol/0.4 nM [92] 1 L C -MS/MS 100 fmol/N.R. [93] 0.75 GC-MS/MS 4 amol/0.125 nM [26] 300-14 000 ELISA ?…”
Section: Artifacts Selectivity Quantitative Overestimates and Falsementioning
confidence: 99%